THE ROLE OF RESONANT LEADERSHIP IN ORGANIZATIONS - Bahar Taner; Berna Aysen (European Scientific Journal, ESJ, 2013)
The changing role of leaders and resonant leadership which is one of the new leadership approaches is investigated. It is observed that compassion, one of the three components of resonant leadership is getting an increasing attention recently in literature. A model is developed focusing on the interaction between compassion and resonant leadership within the context of the relevant variables.